Louis Pasteur: the child is father of the man - Brey, Paul T. (Comptes Rendus Biologies, 2022)
I attempt in this essay to shed new light on the origins of Louis Pasteur’s uniquely progressive mind and spirit and the various factors in his background and upbringing that shaped them. There is, however, very limited documentation on the early period of Pasteur’s life, apart from his son-in-law’s (René Vallery-Radot) biographical account, and this is considered by many as more akin to a work of hagiography. We do have, on the other hand, Pasteur’s correspondence with his parents and sisters as compiled and annotated by his grandson, Louis Pasteur Vallery-Radot. Using these limited sources, combined with what we know about Pasteur’s home environment and early education, his cultural influences (like the books he read), and his drawings and etchings, I have attempted in this essay to hypothesize regarding the influences during Pasteur’s childhood, adolescence, and very early adult years as a scientist and how they contributed to the formation of Pasteur’s mind and spirit, while fully acknowledging the extent to which this is based on indirect evidence and, occasionally, outright speculation.